High‐gain polarization conversion metasurface. Issue 2 (12th January 2019) - Chen, Aixin; Ning, Xiangwei; Liu, Xin; Zhang, Zhe
Abstract : A novel analytical method based on the cavity mode theory to design a metasurface (MS) is proposed in this study. We carefully analyzed the phase and amplitude characteristics of the incident wave and transmitted wave, and successfully designed a circular polarization conversion MS by introducing a cutting structure with wider operation bandwidth and higher radiation direction gain compared with that of the original MS. For the measurements, a microstrip antenna operating at 2.4 GHz was used as the source antenna to verify the designed MS. The simulation and measurement results agree well with each other.